Ginsenosides: Allies of gastrointestinal tumor immunotherapy - Feng, Yutao; Ma, Fen; Wu, Enjiang; Cheng, Zewei; Wang, Zhengtao; Yang, Li; Zhang, Jiwei (Frontiers in Pharmacology, 2022)
Unlike many other common cancers, Gastrointestinal (GI) tumors no longer lack effective treatment methods. The most promising treatments of GI tumors mainly rely on immune regulation, but immunotherapy resistance remains a major concern. It is imperative to develop adjuvant therapies to help immunotherapy against tumor immune response and drug resistance mechanisme Ginseng has been used in Traditional Chinese medicine as an immune booster drug for thousands of years. Its active component, ginsenosides, are candidates for anti-tumor adjuvant therapy, playing an essential role in tumor treatment for decades. They are hypothesized to cooperate with immunotherapy drugs to improve the curative effect and reduce tumor resistance and adverse reactions. This review summarizes the research status of ginsenosides in the immunotherapy of gastrointestinal tumors and discusses its future.